2003
DOI: 10.1046/j.1365-2141.2003.04311.x
|View full text |Cite
|
Sign up to set email alerts
|

Aurora2/BTAK/STK15 is involved in cell cycle checkpoint and cell survival of aggressive non‐Hodgkin's lymphoma

Abstract: Summary. Non‐Hodgkin's lymphoma (NHL) has a wide biological heterogeneity and shows extremely variable responses to therapeutic measures. However, markers that indicate disease activity and determine treatment strategies for this malignancy are little recognized. Using the differential display method, we have identified Aurora2/BTAK/STK15, a centrosome‐associated serine/threonine kinase, whose overexpression leads to centrosome amplification, chromosomal instability and transformation of mammalian solid tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 27 publications
1
36
0
1
Order By: Relevance
“…Expression of Aurora-A can up-regulate telomerase activity and thus promote cell transformation (27). Importantly, amplification and overexpression of Aurora-A have been found in several types of human tumors, including breast cancer (28), hepatocellular cancer (29), bladder cancer (30), testicular germ cell tumors (31), non-Hodgkin's lymphoma (32), and pancreatic cancer (33), although the exact roles of Aurora-A in the development of those tumors are currently under further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of Aurora-A can up-regulate telomerase activity and thus promote cell transformation (27). Importantly, amplification and overexpression of Aurora-A have been found in several types of human tumors, including breast cancer (28), hepatocellular cancer (29), bladder cancer (30), testicular germ cell tumors (31), non-Hodgkin's lymphoma (32), and pancreatic cancer (33), although the exact roles of Aurora-A in the development of those tumors are currently under further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Centrosomes in Aurora A-depleted HeLa cells remained immature (Hirota et al, 2003). Elevated levels of Aurora A have been described in human cancers (Zhou et al, 1998;Sen et al, 2002;Ewart-Toland et al, 2003;Gritsko et al, 2003;Hamada et al, 2003;Li et al, 2003). Aurora A overexpression induces resistance to the chemotherapeutic agent paclitaxel by overriding the spindle checkpoint (Anand et al, 2003).…”
Section: Deregulated Proteolysis In Cancermentioning
confidence: 99%
“…13 Furthermore, we found that AURKA mRNA is overexpressed in a large proportion of freshly isolated human leukemia cells. 6 However, in normal tissues, AURKA mRNA expression is largely limited to the testis.…”
Section: Org Frommentioning
confidence: 91%
“…We have previously shown that testis is the only tissue that expresses detectable levels of AURKA, which suggests that this antigen behaves like cancer/testis antigens. 13 Based on these findings, we previously studied the immunotherapeutic potential of AURKA and identified an HLA-A*0201-restricted antigenic nonamer epitope derived from the kinase domain (residues 207-215). The AURKA 207-215 epitope (YLILEYAPL) was recognized by CD8 ϩ cytotoxic T lymphocytes (CTLs) generated in vitro.…”
Section: Introductionmentioning
confidence: 99%